The FIRED Leader Reinventing the Future of Leadership - McCarthy, Paul (Practical Inspiration Publishing, 2023)
A radical, refreshing, and practical anti-leadership book that addresses the open secret we all know to be true: our current approach to leadership identification, recruitment, onboarding, and development (IROD) isn't working